Strategi Pengembangan Kewirausahaan Pemuda dalam Mendukung Pembangunan Ekonomi Lokal di Kabupaten Merauke (Studi Kasus di Dinas Perindustrian dan Perdagangan, Koperasi, dan UKM) - Franti Mutiara Pricylia Fofied; Coleta Maskikit; Khoriyatun (Jurnal Administrasi Karya Dharma, 2026)
The purpose of this study was to determine the Youth Entrepreneurship Development Strategy in Supporting Local Economic Development in Merauke Regency. Using a descriptive qualitative research approach. The research location was at the Merauke Regency Department of Industry and Trade, Cooperatives and SMEs. The focus of the research used the formulation of development strategies in developing youth entrepreneurship in supporting local economic development, including: mission, objectives, strategies, and policies. Data collection techniques used were observation, interviews, and documentation. The data analysis technique used was qualitative data analysis. The results of the study showed that young people have a high enthusiasm for entrepreneurship as a form of economic independence and contribution to regional development. However, they still face obstacles such as the licensing process which is considered complicated, slow disbursement of business capital assistance, lack of training and business mentoring. Strategies used by young people in advancing their businesses include promotion through social media, product development, and independent business management. Meanwhile, the Department of Industry and Cooperatives has attempted to support through assistance and training programs, but its implementation still faces budget and resource limitations. In conclusion, youth entrepreneurship development plays a crucial role in strengthening the local economy, and therefore requires synergy between local governments and young entrepreneurs to create a sustainable entrepreneurial ecosystem.